Effect of Injection Current on the Normalized Gain Amplitude, Normalized Detuning Coefficient and the Output Power of Axial Distributed Coupling Coefficient Distributed Feedback Laser Diode (ADCC-DFB-LD) - Noori , Mohammed D. (University of Thi-Qar Journal of Science, 2019)
An axial distributed coupling coefficient (ADCC) distributed feedback (DFB) laser diode (LD) in which the coupling coefficient (K) has been distributed axially on both sides of the phase shift region. The effects of injection current on the normalized gain amplitude, normalized detuning coefficient and the output power are investigated using transfer matrix method. The results show that the ADCC DFB laser exhibits high single mode stability at different injection currents above threshold and the main mode operates close to Bragg wavelength at high injected current. For different injection currents the optical output power has been increased with decreased the coupling coefficient.